Agile fusion: developing 'Eat at Right Place' sentiment analysis tool - Akash Prabhune; Vinay R Srihari; Neeraj Kumar Sethiya; Mansi Gauniyal (Institute of Advanced Engineering and Science, 2024)
This study presents the development and validation of the